2015
DOI: 10.1016/j.jmb.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Interaction with RNA Dramatically Enhances the Catalytic Activity of the HIV-1 Protease In Vitro

Abstract: Though the steps of human immunodeficiency virus (HIV)-1 virion maturation are well documented, the mechanisms regulating the proteolysis of the Gag and Gag-Pro-Pol polyproteins by the HIV-1 protease (PR) remain obscure. One proposed mechanism argues that the maturation intermediate p15NC must interact with RNA for efficient cleavage by the PR. We investigated this phenomenon and found processing of multiple substrates by the HIV-1 PR was enhanced in the presence of RNA. The acceleration of proteolysis occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 83 publications
2
21
0
Order By: Relevance
“…We observed that ELISA and Western blot can give differing results for Gag protein levels in the presence of RNA binding agents or RNA structural deletion mutants. These findings resonate with the known effects of RNA on structural stability of HIV virions [ 35 ] and may possibly relate to effects of RNA on Gag processing [ 36 ]. This observation has implications for investigation of viral processes that involve different structural changes in Gag and suggests that results should be validated by Western blots, or by alternative analyses relying on quantification of denatured proteins rather than relying only on methods detecting the native state.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that ELISA and Western blot can give differing results for Gag protein levels in the presence of RNA binding agents or RNA structural deletion mutants. These findings resonate with the known effects of RNA on structural stability of HIV virions [ 35 ] and may possibly relate to effects of RNA on Gag processing [ 36 ]. This observation has implications for investigation of viral processes that involve different structural changes in Gag and suggests that results should be validated by Western blots, or by alternative analyses relying on quantification of denatured proteins rather than relying only on methods detecting the native state.…”
Section: Discussionsupporting
confidence: 80%
“…3a). Since both p66/p66 dimer formation and PR activity may be influenced by ionic strength 36; 37 , and tRNA may act as a polyanion 38–40 , we investigated the impact of different salt concentrations on p66 processing. In the absence of tRNA, at physiological NaCl concentrations (50–150 mM), aberrant non-specific cleavage products (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that packaging of gRNA is important to ensure that the majority of particles adopt a mature, infectious form. It has also recently been demonstrated in vitro that the activity of the HIV-1 protease, itself, is markedly increased in the presence of RNA, although, curiously, the same effect is not observed for the HIV-2 protease [ 106 ].…”
Section: Maturation Of the Viral Corementioning
confidence: 99%